(untitled) (Journal of Nobel Medical College, 2019)
Background: Laparoscopic surgery has various advantages like minimal invasiveness and quick recovery. However carbon dioxide used for pneumoperitoneum during laparoscopic surgery causes increase in heart rate, blood pressure and systemic vascular resistance. The present study compared the efficacy of Dexmedetomidine and Esmolol on hemodynamic responses during laparoscopic cholecystectomy. Material and Methods: A total of 100 patients scheduled for laparoscopic cholecystectomy were randomly allocated in two groups, 50 in each group. Esmolol group received bolus dose of 1 mg/kg intravenous Esmolol just before pneumoperitoneum followed by an infusion of 200 mcg/kg/minand Dexmeditomidine group received bolus dose of 1 mcg/kg iv Dexmedetomidine over 10 minutes before pneumoperitoneum followed by 0.6 mcg/kg/hr in infusion. Hemodynamic parameters like Heart rate, Mean arterial pressure, Systolic blood pressure, Diastolic blood pressure were recorded at different time intervals. Results: It was found that in Dexmeditomidine group there was a statistically significant decrease in heart rate before pneumoperitoneum (84.24±9.17) and 10 minutes after pneumoperitoneum (79.40±7.41)compared to Esmolol Group before pneumoperitoneum (91.40±5.98) and10 minutes after pneumoperitoneum (95.18±14.17).There was statistically significant decrease in Mean arterial pressure in Dexmeditomidine group at 30 minutes (86.53±6.13), 50 minutes (77.95±4.85) , after release of pneumoperitoneum (92.42±3.91) and after extubation (99.50±11.81) compared to Esmolol group at 30 minutes (91.23±8.97), 50 minutes (94.34±12.64) after release of pneumoperitoneum (102.5±10.44) and after extubation (112.39±11.15). Conclusion: Dexmedetomidine was found to be more effective than Esmolol in attenuating the hemodynamic responses following pneumoperitoneum during laparoscopic cholecystectomy.